2021
DOI: 10.1111/ffe.13431
|View full text |Cite
|
Sign up to set email alerts
|

Crack growth measurement and J‐integral evaluation of additively manufactured polymer using digital image correlation and FE modeling

Abstract: This paper presents and compares two combined experimental-numerical techniques for the investigation of fracture properties of additively manufactured polymer parts using digital image correlation (DIC) measurements. The first method only uses measured kinematic fields, and the second is based on Finite Element simulations driven by measured boundary conditions. A mini Single Edge Notched Tensile sample manufactured by fused filament fabrication with ABS is studied. It is shown that both methods locally extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…However, some reported K IC values of FFF-ABS are as low as 0.79 MPa.m 1=2 , given the nonstandard testing practices that were used, that is, introducing a small hole in front of the precrack. 3 In terms of the interlayer fracture toughness, the measurement conducted in the present study (7380 J/m 2 ) is consistent with those measured by Bouaziz et al, 12 but it is much larger than the J values reported in Khosravani et al 10 The discrepancy can be attributed to two testing/ analysis differences: (1) the double cantilever beams had no large deformation correction and (2) no sharp precracks were cut. 10 Figure 4 shows the fracture surfaces of an FFF-ABS specimen (green) and one raw ABS (yellow).…”
Section: Fracture Toughness Changes Of Bulk and Fff-abssupporting
confidence: 89%
See 2 more Smart Citations
“…However, some reported K IC values of FFF-ABS are as low as 0.79 MPa.m 1=2 , given the nonstandard testing practices that were used, that is, introducing a small hole in front of the precrack. 3 In terms of the interlayer fracture toughness, the measurement conducted in the present study (7380 J/m 2 ) is consistent with those measured by Bouaziz et al, 12 but it is much larger than the J values reported in Khosravani et al 10 The discrepancy can be attributed to two testing/ analysis differences: (1) the double cantilever beams had no large deformation correction and (2) no sharp precracks were cut. 10 Figure 4 shows the fracture surfaces of an FFF-ABS specimen (green) and one raw ABS (yellow).…”
Section: Fracture Toughness Changes Of Bulk and Fff-abssupporting
confidence: 89%
“…In additively manufactured (AM) parts, or three‐dimensional (3D) printed parts, defects primarily arise from the layer‐by‐layer nature of the process. Additionally, strength and fracture toughness of AM parts are often anisotropic 2–15 . It is crucial to understand fracture toughness of AM polymers to ensure their reliability and durability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the research [6], a formulation was proposed of the FEM method to analyze crack propagation problems. In addition, a combined comparative study between the two experimental and numerical techniques was presented in research [7] to study the fracture properties of additively fabricated polymer parts using digital image correlation measurement (DIC). In this field, Shafiei [8] studied the influence of geometry on the growth of an inclined crack.…”
Section: Introductionmentioning
confidence: 99%
“…Among these few works, we can cite that of Bouaziz et al who examined in detail the evaluation of cracks in polymers manufactured by FDM based on the concept of integral J. [24].…”
Section: Introductionmentioning
confidence: 99%